Improving drought-, salinity-, and heat-tolerance in transgenic plants by co-overexpressing Arabidopsis vacuolar pyrophosphatase gene AVP1 and Larrea Rubisco activase gene RCA. (July 2020) - Wijewardene, Inosha; Mishra, Neelam; Sun, Li; Smith, Jennifer; Zhu, Xunlu; Payton, Paxton; Shen, Guoxin; Zhang, Hong
Highlights: Over-expressing AVP1 and RCA as linked genes. Increasing plant tolerance to drought, heat, and salt simultaneously. Combining beneficial traits of overexpressing AVP1 and RCA . Co-overexpression of two genes helps plants deal with multiple stresses. Abstract: The severity and frequency of many abiotic stresses such as drought, salinity and heat, cause substantial crop losses worldwide, which poses a serious challenge in food security. To increase crop production, new approaches are needed. Previous research has shown that overexpression of the tonoplast H + pyrophosphatase gene AVP1 leads to improved drought and salt tolerance in transgenic plants. Other research showed that overexpression of thermotolerant ribulose-1, 5-bisphosphate carboxylase/oxygenase (Rubisco) activase gene could maintain photosynthesis at higher temperatures, which contributes to higher heat tolerance in transgenic plants. In nature, abiotic stresses rarely come alone, instead these stresses often occur in various combinations. Therefore, it is desirable to make crops more tolerant to multiple stresses, which will likely lead to higher crop yield under various stress conditions. It is shown here that co-overexpression of the Arabidopsis gene AVP1 and the Larrea Rubisco activase gene RCA significantly increases drought, salinity and heat tolerance, resulting in higher biomass and seed yield than wild-type plants. AVP1/RCA co-overexpressing plants are as more drought- and salt-tolerant as AVP1 -overexpressing plants, and as more heat-tolerant as RCA -overexpressing plants. More importantly, they produce higher seed yields than AVP1 -overexpressing, RCA -overexpressing, and wild-type plants under combined drought and heat conditions.